O professor-performer e a performance educacional: uma política de resistência, escrituras e desvelamentos em desmontagem cênica - Silva, Gleison Amorim da (2018)
This research proposes a performative / collaborative attitude on the part of the readers and revises the artistic processes of genesis that developed the interest of acting with a performance theater. In the process clues, the spectator's point of view is scaled up, mainly by the "mestizaje" of procedures with pedagogical processes, or pedagogical performances. Indicating other possibilities and ways of acting, and amplifying different corporeal revelations in the practices of groups of artists and collectives in Latin America. The idea of acting, especially for pedagogical activity, is oriented in the light of the book "The teacherinterpreter" (CIOTTI, 2014), which outlines these studies on the artistic-pedagogical procedure in “Scenic Disassembly” (CABALLERO, 2009). concept of Disassembly in the context of the extended scene (in performance), we conclude with the dimension of fragmentation practices as pedagogical action, under a more proactive look, and we realize that this research made possible an investigative and methodological course from the moment in which we come to experience them as an experience of artistic / pedagogical work.